2015
DOI: 10.1007/s00213-015-4008-9
|View full text |Cite
|
Sign up to set email alerts
|

Dissociable effects of NR2A and NR2B NMDA receptor antagonism on cognitive flexibility but not pattern separation

Abstract: These data demonstrated that non-selective NMDA antagonism will disrupt numerous aspects of cognitive function. However, selective antagonism is capable of impairing or enhancing cognitive function in a task-dependent fashion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 44 publications
(68 reference statements)
5
40
1
Order By: Relevance
“…Similarly, non-competitive NMDA receptor antagonism in rodents produces behaviors analogous to the positive, negative, and cognitive symptoms of schizophrenia (Moghaddam and Krystal 2012). For example, locomotor hyperactivity (Manahan-Vaughan et al 2008;Howland et al 2012;Zemanova et al 2013;Mahmood et al 2016), reduced sociability (Morales and Spear 2014), and performance deficits on visual learning and working memory tasks (Brown et al 2013;Zemanova et al 2013;Kumar et al 2015b;Kumar et al 2015a;Lins and Howland 2016) are observed following MK-801 administration, mirroring the positive, negative, and cognitive symptoms respectively. Beyond its direct effect on NMDA receptors, MK-801 administration indirectly mimics other pathophysiological features of the disease (Lewis et al 2005).…”
Section: Nmda Receptor Hypofunction As a Model Of Schizophreniamentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, non-competitive NMDA receptor antagonism in rodents produces behaviors analogous to the positive, negative, and cognitive symptoms of schizophrenia (Moghaddam and Krystal 2012). For example, locomotor hyperactivity (Manahan-Vaughan et al 2008;Howland et al 2012;Zemanova et al 2013;Mahmood et al 2016), reduced sociability (Morales and Spear 2014), and performance deficits on visual learning and working memory tasks (Brown et al 2013;Zemanova et al 2013;Kumar et al 2015b;Kumar et al 2015a;Lins and Howland 2016) are observed following MK-801 administration, mirroring the positive, negative, and cognitive symptoms respectively. Beyond its direct effect on NMDA receptors, MK-801 administration indirectly mimics other pathophysiological features of the disease (Lewis et al 2005).…”
Section: Nmda Receptor Hypofunction As a Model Of Schizophreniamentioning
confidence: 99%
“…Thus, the first objective of this research is to demonstrate the face validity of the MK-801 model of schizophrenia in the TUNL task. Only one previous study has investigated performance changes following acute MK-801 administration in the TUNL task (Kumar et al 2015a). The results of this experiment showed 0.05 mg/kg of MK-801 impaired task accuracy with 1 s and 20 s delays.…”
Section: Rationale and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…First, these tasks were applied in rats in some studies (Talpos et al 2014;Kumar et al 2015). The dPAL task was shown to be sensitive to pharmacological inhibition of hippocampal activity (Talpos et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The dPAL task was shown to be sensitive to pharmacological inhibition of hippocampal activity (Talpos et al 2009). In addition, this task was used to test the effect of antagonism of various Nmethyl-d-aspartate receptor subtypes in rats (Kumar et al 2015). The PAL task has also been used in mice in various studies (Bartko et al 2011b;Delotterie et al 2015;Kim et al 2015).…”
Section: Introductionmentioning
confidence: 99%